The effect of herbal medicine in reducing the severity of oral lichen planus: A systematic review and meta-analysis - Kharissa Kemala Vychaktami; Rahmi Amtha; Indrayadi Gunardi; Rosnah Binti Zain (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2022)
Background: Oral lichen planus (OLP) is a chronic autoimmune mucocutaneous disease of unknown aetiology. The reported use of herbal medicines may promote the healing of OLP lesions. Purpose: We aim to determine the effectiveness of herbal medicine to reduce the clinical and pain severity of OLP. Methods: PubMed, Cochrane Library and Wiley Online Library were reviewed according to the inclusion criteria. Risk of bias was performed for the randomised control trial (RCT) and cohort studies to assess the effectiveness of herbal medicines for OLP treatment. Outcomes were recorded based on pain severity and the quality of life of patients with OLP. The mean difference and effect size of studies were pooled. Reviews: Out of 1,034 papers, six publications were selected and reviewed. The most common types of OLP lesions were erosive and atrophic and were mainly found at the buccal site. OLP was common in the range of 27–74 years, especially in females. The herbal medicines used in the publication were curcumin, lycopene, purslane, aloe vera and quercetin. Improvement in quality of life or OLP severity was recorded in the intervention group treated with purslane, curcumin and lycopene (P<0.05) but not in the control group. The total effect of herbal medicine in reducing pain severity (measured with the Visual Analogue Scale [VAS]) in OLP patients was not significant (mean difference 0.13; 95% CI -0.202 to 0.463; p=0.442). Conclusions: Herbal medicine cannot be used as a single regime to reduce pain severity. Further research is recommended to evaluate cohort design studies to observe the prolonged effect of herbal medicine in OLP lesions. PROSPERO registration number: CRD42021262282 (2021)